Translational Pharmacokinetic–Pharmacodynamic Modeling of NaV1.7 Inhibitor MK-2075 to Inform Human Efficacious Dose - Ballard, Jeanine E.; Pall, Parul S.; Vardigan, Joshua; Zhao, Fuqiang; Holahan, Marie A.; Zhou, Xiaoping; Jochnowitz, Nina; Kraus, Richard L.; Klein, Rebecca M.; Henze, Darrell A.; Houghton, Andrea K.; Burgey, Christopher S.; et al. (Frontiers in Pharmacology, 2021)
MK-2075 is a small molecule selective inhibitor of the NaV1.7 channel investigated for the treatment of post-operative pain. A translational strategy was developed for MK-2075 to quantitatively interrelate drug exposure, target modulation, and desired pharmacological response in preclinical animal models for the purpose of human translation. Analgesics used as standard of care (SOC) in post-operative pain were evaluated in preclinical animal models of nociceptive behavior (mouse tail flick latency and rhesus thermode heat withdrawal) to determine the magnitude of pharmacodynamic response at plasma concentrations associated with efficacy in the clinic. MK-2075 was evaluated in those same animal models to determine the concentration of MK-2075 required to achieve the desired level of response. Translation of MK-2075 efficacious concentrations in preclinical animal models to a clinical PKPD target in human was achieved by accounting for species differences in plasma protein binding and in vitro potency against the NaV1.7 channel. Estimates of human PK parameters were obtained from allometric scaling of PK from preclinical species and used to predict the dose required to achieve the clinical exposure. MK-2075 exposure-response in a preclinical target modulation assay (rhesus olfaction) was characterized using a computational PKPD model which includes a biophase compartment to account for the observed hysteresis. Translation of this model to humans was accomplished by correcting for species differences in pharmacokinetics, NaV1.7 potency, and plasma protein binding while assuming the kinetics of distribution to the target site is the same between human and rhesus. This enabled prediction of the level of target modulation anticipated to be achieved over the dosing interval at the projected clinical efficacious human dose. Integration of these efforts into the early development plan informed clinical study design and decision criteria.